A Daytime Nap Does Not Enhance the Retention of a First-Order or Second-Order Motor Sequence - Barham, Michael P.; Lum, Jarrad A. G.; Conduit, Russell; Fernadez, Lara; Enticott, Peter G.; Clark, Gillian M. (Frontiers in Behavioral Neuroscience, 2021)
This study examined the effects of a daytime nap on the retention of implicitly learnt ‘first-order conditional’ (FOC) and ‘second-order conditional’ (SOC) motor sequences. The implicit learning and retention of a motor sequence has been linked to the neural processes undertaken by the basal ganglia and primary motor cortex (i.e., procedural memory system). There is evidence, however, suggesting that SOC learning may further rely on the hippocampus-supported declarative memory system. Sleep appears to benefit the retention of information processed by the declarative memory system, but not procedural memory system. Thus, it was hypothesised that sleep would benefit the retention of an SOC motor sequence but not FOC sequence. The implicit learning and retention of these sequences was examined using the Serial Reaction Time Task. In this study, healthy adults implicitly learnt either a FOC (n = 20) or a SOC sequence (n = 20). Retention of both sequences was assessed following a daytime nap and period of wakefulness. Sleep was not found to improve the retention of the SOC sequence. There were no significant differences in the retention of a FOC or a SOC sequence following a nap or period of wakefulness. The study questions whether the declarative memory system is involved in the retention of implicitly learnt SOC sequences.